A Web-Based Irrigation Scheduling Model to Improve Water Use Efficiency and Reduce Nutrient Leaching for Florida Citrus - Kelly T. Morgan; Edward A. Hanlon; Thomas A. Obreza (EDIS)
SL286, a 4-page illustrated fact sheet by Kelly T. Morgan, Edward A. Hanlon, and Thomas A. Obreza, describes an easy to use web-based water-balance irrigation scheduling tool that assists growers in determining irrigation schedules that can improve water use efficiency and reduce nutrient leaching. Published by the UF Department of Soil and Water Science, May 2009.